Effect of spironolactone on transmitral diastolic blood flow and course of chronic heart failure with preserved left ventricular ejection fraction - V. A. Vasylenko (Zaporožskij Medicinskij Žurnal)
Existing recommendations on the mineralocorticoid/aldosterone receptor antagonists have been developed only for patients with systolic heart failure, and all outcome trials performed in patients with preserved ejection fraction failed to improve prognosis in this condition.